A peptide derived from TID1S rescues frataxin deficiency and mitochondrial defects in FRDA cellular models - Dong, Yi Na; Ngaba, Lucie Vanessa; An, Jacob; Adeshina, Miniat W.; Warren, Nathan; Wong, Johnathan; Lynch, David R. (Frontiers in Pharmacology, 2024)
Friedreich's ataxia (FRDA), the most common recessive inherited ataxia, results from homozygous guanine-adenine-adenine (GAA) repeat expansions in intron 1 of the FXN gene, which leads to the deficiency of frataxin, a mitochondrial protein essential for iron-sulphur cluster synthesis. The study of frataxin protein regulation might yield new approaches for FRDA treatment. Here, we report tumorous imaginal disc 1 (TID1), a mitochondrial J-protein cochaperone, as a binding partner of frataxin that negatively controls frataxin protein levels. TID1 interacts with frataxin both in vivo in mouse cortex and in vitro in cortical neurons. Acute and subacute depletion of frataxin using RNA interference markedly increases TID1 protein levels in multiple cell types. In addition, TID1 overexpression significantly increases frataxin precursor but decreases intermediate and mature frataxin levels in HEK293 cells. In primary cultured human skin fibroblasts, overexpression of TID1S results in decreased levels of mature frataxin and increased fragmentation of mitochondria. This effect is mediated by the last 6 amino acids of TID1S as a peptide made from this sequence rescues frataxin deficiency and mitochondrial defects in FRDA patient-derived cells. Our findings show that TID1 negatively modulates frataxin levels, and thereby suggests a novel therapeutic target for treating FRDA.